GENETICS OF HUMAN HEREDITARY HEARING IMPAIRMENT - Meena, Rahat; Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 2017)
Hereditary hearing impairment is heterogeneous type of disorder which can be caused due to environmental as well as genetical factors. Two distinct types of hereditary hearing loss are syndromic or non-syndromic. Non-syndromic hearing loss is further categorized as autosomal recessive, autosomal dominant, X-linked and mitochondrial deafness. Autosomal recessive occurs more frequently as compared to autosomal dominant. Mutations in various genes are responsible for hereditary hearing impairment. To date, about 99 autosomal recessives and 67 autosomal dominant genes for deafness have been discovered. Some of important genes include GJB2, JGB6, GJB3 which encodes gap junction proteins, MYO7A, MYO15A encodes myosine proteins, OTOF encodes otoferlin, and SLC26A4 encodes anion exchanger protein. Up till now, the mutation in GJB2 gene occurs more frequently in different population of the world and cause autosomal recessive hearing impairment. The purpose of this review article was to explore the mutation and function of those muted genes which encode different type of protein and responsible either for autosomal recessive or autosomal dominant hearing impairment. Keywords: Recessive deafness, Dominant deafness, Mutation, Encoded proteins, Genetics